Ben Delatour Scout Ranch - Forest Fuel Reduction - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2003)
Located in: Fort Collins office files. Ben Delatour Scout Ranch documentation related to Colorado State Forest Service Western States Wildlife Urban Interface project and State Fire Assistance grants, years 2003 to 2005 for forest fuel reduction and fire mitigation. Includes: reports, communication, forestry reports, program payment requests, expense records to include invoices, receipts and log sheets.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado